The Lake District Murder - Bude, John, 1901-1957 (British Library crime classics., 2016)
The Lake District Murder opens with the discovery of a faceless body in an isolated garage, then follows Inspector Meredith through a complex investigation where every clue seems to lead only to another puzzle. Was this a bizarre suicide, or something more sinister? Why was the dead man apparently making plans to flee the country? And what does all this have to do with the newly discovered shady business dealings of the garage?